2007
DOI: 10.1002/chem.200700600
|View full text |Cite
|
Sign up to set email alerts
|

Linking Two Distinct Layered Networks of Nanosized {Ln18} and {Cu24} Wheels through Isonicotinate Ligands

Abstract: A new series of heterolanthanide(III)-copper(I) wheel-cluster complexes [Ln6(micro3-O)2](IN)18-[Cu8(micro4-I)2(micro2-I)3].H3O (IN=isonicotinate; Ln=Y 1, Nd 2, Dy 3, Gd 4, Sm 5, Eu 6, Tb 7) were prepared by hydrothermal reaction at low pH. X-ray crystallographic studies reveal that two unusual trinuclear [Ln3(micro3-O)] and tetranuclear [Cu4(micro4-I)] cores are successfully used as secondary building units to make two different nanosized wheels [Ln18(micro3-O)6(CO2)48](6-), {Ln18}, and [Cu24(micro4-I)6(micro2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(46 citation statements)
references
References 88 publications
(47 reference statements)
1
43
1
1
Order By: Relevance
“…Each 12 ] clusters by coordinating deprotonated carboxylic group oxygen atoms to Co3 atoms from three different clusters, as shown in Figure 1b …”
Section: Crystal Structures Of 1-co 13 Mg 2 2-co 13 Ca 2 and 4-mg 15mentioning
confidence: 98%
See 1 more Smart Citation
“…Each 12 ] clusters by coordinating deprotonated carboxylic group oxygen atoms to Co3 atoms from three different clusters, as shown in Figure 1b …”
Section: Crystal Structures Of 1-co 13 Mg 2 2-co 13 Ca 2 and 4-mg 15mentioning
confidence: 98%
“…X-ray analyses revealed that compound 1 contains thirteen cobalt(II) ions, two magnesium(II) ions, six PMIDA 4- 12 ], as shown in Figure 1a. There are three crystallographically independent cobalt atoms and one crystallographically independent magnesium atom in each asymmetric unit, which exhibit regular distribution.…”
Section: Crystal Structures Of 1-co 13 Mg 2 2-co 13 Ca 2 and 4-mg 15mentioning
confidence: 99%
“…Although many interesting coordination polymeric frameworks are constructed by rational selection of multi-dentate bridging organic ligand as "spacer" and the metal ion or multi-core metal cluster as "node" [6][7][8] , much attention has been paid to the assembly of mixed 3d transition metals (TM) [9,10] , while the 3d-4f heterometallic polymers have received less attention [11][12][13][14][15][16] , mainly because the competitive reactions between 3d and 4f metals chelated to the same ligand often lead to homometallic polymers rather than heterometallic ones. Recently, we have explored the synthesis of the 3d-4f heterometallic polymers, and successfully obtained a series of 3-D Ln-TM wheel cluster polymers [Er 7 (μ 3 -O)(μ 3 -OH) 6 (bdc) 3 ](ina) 9 [Cu 3 X 4 ] (X = Cl or Br, H 2 bdc=1,2-benzenedicarboxylic acid, Hina = isonicotinic acid) [12] and [Ln 6 (μ 3 -O) 2 ](IN) 18 [Cu 8 (μ 4 -I) 2 -(μ 2 -I) 3 ]·H 3 O (HIN = isonicotinate acid ; Ln = Y, Nd, Dy, Gd, Sm, Eu, Tb) [13] , 3-D Ln-TM nanosized hydroxo-Ln cluster polymers [Ln 14 (μ 6 -O)(μ 3 -OH) 20 [14] , and 3-D Ln-TM pillared-layer polymers Ln 2 (bdc) 2 (ina) 2 (H 2 O) 2 Cu·X (H 2 bdc = 1,2-benzenedicarboxylic acid; Ln = Eu, Sm, Nd, X = ClO 4  ; Ln = Nd, X = Cl  ) [15] , Ln 2 Cu 7 I 6 (ina) 7 -(H 2 O) 6 ·H 2 O (Ln = Ce, Sm) and Er 4 (OH) 4 Cu 5 I 4 (ina) 6 (na)-(2,5-pdc)·0.3H 2 O (Hna = nicotinic acid, 2,5-H 2 pdc = 2,5-pyridinedicar-boxylic acid) [16] . The structures of these 3-D Ln-TM polymers are based on multi-core metal cluster as "node" and bridging organic ligand with pyridine functional group as "spacer".…”
Section: A New 3-d Porous Gd-cu Heterometallic Polymer [Gd 2 Cu 3 (Bpmentioning
confidence: 99%
“…S4). The Yb\O bond lengths range from 2.210(6) to 2.371(6)Å, with an average value of about 2.276 Å (Table S1), shorter than some documented seven-coordinated trivalent lanthanide ions with larger ionic radii [24]. Ag(1) adopts a distorted tetrahedron coordination geometry with an N 2 O 2 donor set.…”
mentioning
confidence: 99%